Associations of movement behaviours and dietary intake with arterial stiffness: results from the ORISCAV-LUX 2 cross-sectional study - Saverio Stranges; Ala’a Alkerwi; Guy Fagherazzi; Laurent Malisoux; Michel Vaillant; Isabelle Ernens; Manon Gantenbein; Laetitia Huiart; Jean-Claude Schmit; Dritan Bejko; Anne Backes; Farhad Vahid; et al. (BMJ Open)
Objective Adopting a physically active lifestyle and maintaining a diet rich in antioxidants can reduce the risk of vascular diseases. Arterial stiffness is an early marker for cardiovascular diseases, indicating vascular damage. This study investigates the relationship between physical activity (PA), sedentary behaviour (SB), dietary antioxidant, trace elements intake and vascular health in men and women, with a focus on pulse wave velocity (PWV), the gold standard for assessing arterial stiffness.Design This is a nationwide population-based cross-sectional study (Observation of Cardiovascular Risk Factors in Luxembourg 2 (ORISCAV-LUX 2)).Setting The study was conducted in Luxembourg, between November 2016 and January 2018.Participants In total, 988 participants from the ORISCAV-LUX 2 study, who were Luxembourg residents, aged 25–79 years, underwent the required physical examination, agreed to wear an accelerometer for 1 week and presented no personal history of myocardial infarction or stroke, were included in the analysis.Primary outcome measure PWV was assessed with the validated Complior instrument. Elastic-net models were used to investigate the associations of dietary intake (antioxidant and trace elements) and movement behaviours (PA and SB) with PWV in men and women.Results The findings reveal diverse associations between PA, SB, dietary intake and PWV, with distinct patterns observed in men and women. In women, a longer median moderate-to-vigorous PA bout length (mean coefficient (β)=−0.039), a higher long-range temporal correlation (higher scaling exponent alpha) at larger time scales (>120 min; β=−1.247) and an increased intake of vitamin C (β=−1.987) and selenium (β=−0.008) were associated with lower PWV. In men, a shorter median SB bout length (β=0.019) and a lower proportion of SB time accumulated in bouts longer than 60 min (β=1.321) were associated with lower PWV. Moreover, a higher daily intake of polyphenols (β=−0.113) and selenium (β=−0.004) was associated with lower PWV in men.Conclusion This study underscores the multifaceted nature of the associations between movement behaviours and dietary intake with PWV, as well as sex differences. These findings highlight the significance of considering both movement behaviours and dietary antioxidant intake in cardiovascular health assessments.